PENGARUH BEBAN KERJA, KOMPENSASI DAN WORK-LIFE BALANCE TERHADAP KINERJA KARYAWAN PADA PT PITJARUS TEKNOLOGI - Nida Luthfi Azizah; Indah Rizki Maulia; Adi Wibowo Noor Fikri; Neng Siti Komariah; Jumawan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the extent to which workload, compensation, and work-life balance influence employee performance and their impact on PT Pitjarus Teknologi. The background of this research is based on the phenomenon of declining employee performance, as indicated by lateness, excessive workload, unsatisfactory compensation, and an imbalance between work and personal life. This research employs a quantitative method with a descriptive and verification approach. The population in this study consists of all employees of PT Pitjarus Teknologi located in Bekasi City. The sampling technique used is purposive sampling. Data were collected through the distribution of a questionnaire via Google Forms, with a total sample of 60 respondents, and analyzed using SmartPLS 4.0 statistical software. The results of the study show that the workload variable partially has a positive but not significant effect on employee performance; the compensation variable also has a positive but not significant effect; while the work-life balance variable partially has a positive and significant effect on employee performance. Based on these findings, it can be concluded that there are other factors that positively and significantly influence employee performance.